Kontribusi Pemikiran Pendidikan Imam Al-Ghazāli (1058-1111 M) dan Yūsuf Al-Qarḍāwi (1926 M) dalam Menghadapi Problematika Pendidikan Islam di Indonesia Dewasa Ini - Basa'ad, Tazkiyah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2013)
This article presents that Imam al-Ghazali and Yusuf al-Qardawi have contributed significantly to the Islamic education paradign today. The concept of Islamic education should be developed so that it is compatible to modern education without ignoring religious values. Therefore, to deal with some problems in Islamic education is to think over again the concept of education ofÂ Imam al-Ghazali and YusufÂ al-Qardawi. That is, their thoughts are still relevant to the present settings and provide possible solution to the present education problems.